Mindfulness, Spirituality, and Work Balance in the Workplace: Increasing Productivity and Reducing Work-Life Disruptions - Fadli Adam; Nizar Zulfahmi Azhar; Sandi Nasrudin Wibowo (Indonesian Journal of Business Analytics, 2024)
Human resources or what are usually called employees are an important aspect of a company in achieving predetermined goals. To be able to achieve company goals, good performance productivity from employees is required. The importance of work productivity, so efforts are needed to minimize various disruptions to work life. The factors to increase productivity and reduce work life disruptions are mindfulness, spirituality and work balance. This study aims to explore the Workplace mindfulness, spirituality and work-life balance are factors that have the potential to influence individuals' performance and well-being at work. The method used is quantitative. This research uses two data collection techniques, namely questionnaires and literature study. The research results show that mindfulness, spirituality, and work balance have a significant effect on increasing productivity and reducing work-life disruption. This research suggests the need for the integration of mindfulness programs, emotional skills training, and an organizational culture that supports spirituality in the workplace. With a focus on work-life balance, this can improve overall employee productivity, well-being and satisfaction, creating a healthier and more productive work environment.